Priors in Animal and Artificial Intelligence: Where Does Learning Begin?. Issue 11 (November 2018) - Versace, Elisabetta; Martinho-Truswell, Antone; Kacelnik, Alex; Vallortigara, Giorgio
Abstract : A major goal for the next generation of artificial intelligence (AI) is to build machines that are able to reason and cope with novel tasks, environments, and situations in a manner that approaches the abilities of animals. Evidence from precocial species suggests that driving learning through suitable priors can help to successfully face this challenge.